Audit Quality Perceptions and Capital Market Confidence Effects (gjstudies, 2018)
This research investigates the underexplored cognitive and behavioral mechanismsthrough which perceptions of audit quality, distinct from objective quality measures,influence capital market confidence. Moving beyond traditional archival studies linkingaudit firm size or fees to market outcomes, we propose a novel theoretical framework integrating signal processing theory from information science with institutional trust constructs from sociology. We conceptualize the audit report not merely as an informationsignal but as a complex trust anchor, whose interpretation by market participants is mediated by perceptual filters shaped by narrative disclosures, media sentiment, and theauditor’s communicative persona. The methodology employs a hybrid computationalempirical approach, combining natural language processing of audit report narrativesand related financial news from 1998-2004 with an experimental asset market simulation. We analyze linguistic features—such as certainty tone, explanatory depth, andrhetorical complexity—to construct a Perceived Assurance Strength (PAS) index. Thisindex is then used as a treatment variable in controlled market simulations with professional analysts. Our results reveal a non-linear, threshold-dependent relationshipbetween PAS scores and trading confidence metrics, such as bid-ask spread volatilityand order book depth. Crucially, we find that high PAS scores can, under specific conditions of market uncertainty, decouple from underlying audit rigor and independentlybolster confidence, presenting a potential ’perception premium.’ Conversely, a low PASscore has a disproportionately negative effect, suggesting an asymmetry in perceptualimpact. The study concludes that the market’s confidence ecosystem is significantlyshaped by the stylistic and narrative dimensions of audit communication, which actas heuristics for trust. This reframes audit quality as a dual construct: technical and1Published: 2018-02-01presentational. The originality of this work lies in its cross-disciplinary lens, its focuson the semiotics of audit reporting, and its demonstration of how perceptual artifacts,once formed, become tangible market forces. These insights contribute to auditingtheory, financial communication, and market regulation by highlighting the need toconsider the architecture of perception alongside the architecture of standards.